Penerapan Teknologi Digital melalui Pemetaan Lokasi UMKM di Google Maps untuk Meningkatkan Aksesibilitas Konsumen di Destinasi Wisata Bukit Lawang - Ricky Widyanto; Eriana Saprida; Muhammad Fadlan; M Sahlan; Heru Syahputra (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
The community service program entitled “Implementation of Digital Technology through Mapping MSME Locations on Google Maps to Enhance Consumer Accessibility in the Bukit Lawang Tourism Area” aims to improve digital literacy and business visibility among local micro, small, and medium enterprises (MSMEs) in Bukit Lawang, Langkat Regency, North Sumatra. The program was carried out using a participatory approach through socialization, training, and technical assistance involving four local MSMEs, consisting of two wildlife-themed painting craftsmen, one culinary business, and one souvenir craftsman. The results show that all MSMEs were successfully registered and verified on Google Maps, leading to increased consumer accessibility and customer interaction through digital reviews. In addition to expanding market reach, this activity also fostered awareness and independence among business owners in managing their online business profiles. This program demonstrates that location mapping through Google Maps serves as a simple yet effective strategy to support MSME digital transformation and strengthen community-based creative economies in rural tourism areas.